Our Instruments are Our Masks: Developing Communication Skills and Confidence Through Collective Free Improvisation - Ladano, Kathryn (Critical Studies in Improvisation / Études critiques en improvisation, 2022)
This study explores the idea that musical instruments can function as masks in the context of collective free improvisation. Just as masks are used in theatre improvisation to build confidence and facilitate creative expression, musicians can use their instruments in similar ways, increasing their level of comfort and allowing them to connect and communicate with others in ways not available through traditional social exchanges. Through a variety of interviews, questionnaires, and performances, 30 instrumentalists and vocalists participated in this study and shared their experiences performing with their peers. Through analysis of recorded performances, interview and questionnaire responses, it was discovered that the vast majority of participants identified with the idea that their instruments functioned as masks. Most of these individuals believed their instruments helped them express parts of themselves that could not be expressed through other means, and many believed their instruments allowed for the creation of a persona, in which they felt they could “be” someone else when performing. Participants were in agreement that they only felt their instruments functioned this way in the context of collective free improvisation. The strong feelings of connection, confidence, and communication experienced by participants strengthen the case for incorporating free improvisation into music education.